First record of Lonomia camox Lemaire, 1971 (Lepidoptera, Saturniidae) in Brazil - Xavier Filho, Francisco Felipe; Lourido, Gilcélia Melo (EntomoBrasilis, 2023)
Lonomia Walker, 1855 is a genus of Lepidoptera belonging to the Saturniidae whose caterpillars have a defense system based on scoli connected to venom glands, which can cause medical accidents of envenomation, thereby making this genus medically important. In this work, Lonomia camox Lemaire, 1971, is recorded for the first time in Brazil, more specifically in the state of Amazonas. Photographs of male and female genitalia and an updated map with new occurrence records are presented.